2017
DOI: 10.1038/s41598-017-17985-9
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Rectifying Properties of the n-3C-SiC/p-Si Heterojunction Subjected to High Temperature Annealing for Electronics, MEMS, and LED Applications

Abstract: This work examines the stability of epitaxial 3C-SiC/Si heterojunctions subjected to heat treatments between 1000 °C and 1300 °C. Because of the potential for silicon carbide in high temperature and harsh environment applications, and the economic advantages of growing the 3C-SiC polytype on large diameter silicon wafers, its stability after high temperature processing is an important consideration. Yet recently, this has been thrown into question by claims that the heterojunction suffers catastrophic degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…The crystal defects, mainly stacking faults, as well as film quality can be improved by carbonizing the active silicon surface before the deposition of 3C-SiC [10], [11]. A number of studies have reported that, despite the presence of crystal defects at the interface, 3C-SiC/Si heterojunction show excellent diode characteristics with a large valance band offset (1.7 eV) between SiC and Si [12]- [14]. As such, the large effective barrier height could be very useful for many applications, such as piezoresistive sensors [6], piezo-Hall devices [15], and biomedical applications [16], where electrical isolation between 3C-SiC and Si is essential.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal defects, mainly stacking faults, as well as film quality can be improved by carbonizing the active silicon surface before the deposition of 3C-SiC [10], [11]. A number of studies have reported that, despite the presence of crystal defects at the interface, 3C-SiC/Si heterojunction show excellent diode characteristics with a large valance band offset (1.7 eV) between SiC and Si [12]- [14]. As such, the large effective barrier height could be very useful for many applications, such as piezoresistive sensors [6], piezo-Hall devices [15], and biomedical applications [16], where electrical isolation between 3C-SiC and Si is essential.…”
Section: Introductionmentioning
confidence: 99%
“…The carbon interstitials can behave as deep acceptors in silicon with an activation energy of 0.35 eV from the valence band (hole traps) 23 , and assist compensation of unintentional donors in the SiC film as well as hole injection from the Si substrate across the Si/SiC interface further reducing the effectiveness of p-n junction. 4 Hence, the generation of a considerable amount of interstitial carbon defects in the top portion of silicon upon high temperature epitaxy, would explain both the mechanical and the electrical behaviour observed in the SiC/Si system.…”
Section: Discussion and Modelmentioning
confidence: 99%
“…2 Despite these significant properties, no 3C-SiC based devices are currently commercially available 3 and this is due in part to problems associated with SiC/Si junctions. [4][5][6] We have recently shown that the expected p-n junction between a p-type silicon substrate to the 3C-SiC, naturally grown as unintentionally n-type, is either non-existing or very unstable so that severe leakage or even plain shorting of the epitaxial silicon carbide to the underlying silicon substrate 1 is typically found. 7,8 The absence of a stable p-n junction at the SiC/Si interface could pose important limitations to the applications of 3C-SiC in power electronics, harsh environment, MEMS, LEDs, graphene-based devices, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a high density of defects characterizes the region where the 3C-SiC/Si interface is, due to inherent lattice (20%) mismatch and differences in the thermal expansion coefficients [7], [50] between the two materials. For a representative device model of vertical diodes, the inclusion of these 3C-SiC deep levels is required.…”
Section: A Validation Of the 3c-sic Physical Modelmentioning
confidence: 99%